2020
DOI: 10.1017/s0952523820000048
|View full text |Cite
|
Sign up to set email alerts
|

Of neurons and pericytes: The neuro-vascular approach to diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a frequent complication of diabetes mellitus and an increasingly common cause of visual impairment. Blood vessel damage occurs as the disease progresses, leading to ischemia, neovascularization, blood–retina barrier (BRB) failure and eventual blindness. Although detection and treatment strategies have improved considerably over the past years, there is room for a better understanding of the pathophysiology of the diabetic retina. Indeed, it has been increasingly realized that DR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
0
6
0
2
Order By: Relevance
“…After activating the synaptic receptor, extracellular glutamate is transferred into Müller cells by binding the glutamate aspartate transporter (GLAST), subsequently converted to glutamine under the action of the enzyme glutamine synthetase (GS) ( 111 ). Following this, glutamine is secreted into the extracellular space by Müller cells whereupon neurons can take in and then transform it into GABA or glutamate ( 112 ). Once this balance was disturbed, such as by hyperglycemia, accumulation of glutamate, reduced GS activity, and resultant loss of neuronal glutamine availability would be observed, which would lead to glutamate excitotoxicity, i.e., further retinal physiological disruptions that involved oxidative stress, inflammation, and neuronal apoptosis ( 112 , 113 ).…”
Section: Analysis and Elucidation Of Common Differential Metabolites ...mentioning
confidence: 99%
“…After activating the synaptic receptor, extracellular glutamate is transferred into Müller cells by binding the glutamate aspartate transporter (GLAST), subsequently converted to glutamine under the action of the enzyme glutamine synthetase (GS) ( 111 ). Following this, glutamine is secreted into the extracellular space by Müller cells whereupon neurons can take in and then transform it into GABA or glutamate ( 112 ). Once this balance was disturbed, such as by hyperglycemia, accumulation of glutamate, reduced GS activity, and resultant loss of neuronal glutamine availability would be observed, which would lead to glutamate excitotoxicity, i.e., further retinal physiological disruptions that involved oxidative stress, inflammation, and neuronal apoptosis ( 112 , 113 ).…”
Section: Analysis and Elucidation Of Common Differential Metabolites ...mentioning
confidence: 99%
“…In an animal model of traumatic brain injury (TBI), it was observed that an impairment of platelet-derived growth factor-B (PDGF-B) signaling, resulting in a loss of pericyte–endothelium interaction and consequent neurovascular dysfunction, correlates with reduced levels of N-cadherin, adherent junction, and Cx43 functionality [ 175 ]. A noteworthy finding is the decline and/or reduction in Cx43–GJs along the arteriole–capillary vascular pathway; this is considered one of the first indicators of experimental diabetic retinopathy associated with reduced propagative vasomotor activity and cell coupling as well as compromised anatomical and physiological integrity of the retina [ 176 ].…”
Section: Overview and Concluding Remarksmentioning
confidence: 99%
“…Blood vessel damage arises with disease advancement, with subsequent ischemia, neovascularization, blood–retina barrier (BRB) disruption, and subsequent blindness. Though research work and treatment strategies have been established noticeably over the former years, there is a scope for an improved understanding of the pathophysiology and biochemical alterations concerning the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%